Multiplex PCR genotyping for five bacterial blight resistance genes applied to marker‐assisted selection in rice (Oryza sativa). Issue 3 (June 2016) - Yap, Ruishen; Hsu, Yu‐Chia; Wu, Yong‐Pei; Lin, Yann‐Rong; Kuo, Chei‐Wei
Abstract: Bacterial blight (BB) is the most economically damaging disease of rice in Asia and other parts of the world. In this study, a multiplex PCR genotyping method was developed to simultaneously identify genotypes of five BB resistance genes, Xa4, xa5, Xa7, xa13 and Xa21 . The resistance R alleles were amplified using five functional markers (FMs) to generate amplicons of 217, 103, 179, 381 and 595 bp in IRBB66. Amplicons of 198, 107, 87, 391 and 467 bp corresponded to susceptible alleles in Taiwanese japonica rice cultivars. In backcross breeding programmes, the multiplex PCR assay was integrated into selection from a population using BB resistance donor IRBB66 crossed to rice cultivar 'Tainung82'. Two plants with homozygosity for Xa4, xa5, Xa7, xa13 and Xa21 were selected from 1100 BC2 F2 plants. In addition, the five BB resistance genes were also accurately identified in F2 populations. This multiplex PCR method provides a rapid and efficient method for detecting various BB resistance genes, which will assist in pyramiding genes to improve durability of BB resistance in Taiwanese elite rice cultivars.